Efficacy of probiotics for managing infantile colic due to their anti-inflammatory properties: a meta-analysis and systematic review - Reza Shirazinia; Ali Akbar Golabchifar; Mohammad Reza Fazeli (The Korean Pediatric Society, 2021)
Background Infantile colic (IC) is excessive crying in otherwise healthy children. Despite vast research efforts, its etiology remains unknown. Purpose Most treatments for IC carry various side effects. The collection of evidence may inform researchers of new strategies for the management and treatment of IC as well as new clues for understanding its pathogenesis. This review and meta-analysis aimed to evaluate the efficacy and possible mechanisms of probiotics for mananaging IC. Methods Ten papers met the study inclusion and exclusion criteria, and the meta-analysis was conducted using Review Manager (RevMan) software and a random-effects model. Results This meta-analysis revealed that probiotics are effective for treating infantile colic, while the review showed that this efficacy may be due to their anti-inflammatory effects. Conclusion Probiotics may be an important treatment option for managing infantile colic due to their anti-inflammatory properties.